2018
DOI: 10.1038/s41598-018-27156-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol mixing state matters for particles deposition in human respiratory system

Abstract: Aerosol particles emitted from various human activities deteriorate air quality and are suggested to increase public health risk. Numerous studies have emphasized the relationship between the mass and/or number concentration of aerosols (or commonly known as particulate matter (PM)) in the atmosphere and the incidence of respiratory and cardiovascular diseases, while very few have examined the deposition efficiency of inhaled particles in the respiratory tract. We present the first examination of particles dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 46 publications
2
50
0
3
Order By: Relevance
“…Detailed single particle analysis contributes to aerosol model development and evaluation to explore the underlying interplay between emission, meteorology and chemistry governing the physicochemical properties evolutions, the highly uncertain aerosol-cloud-climate interaction and the associated impacts on climate 5,11,45 and air quality. 13,14 This consequently benefits air quality prediction, and pollution mitigation policy devising and aligns with one of the emphases in the theme of sustainable development. 46,47…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Detailed single particle analysis contributes to aerosol model development and evaluation to explore the underlying interplay between emission, meteorology and chemistry governing the physicochemical properties evolutions, the highly uncertain aerosol-cloud-climate interaction and the associated impacts on climate 5,11,45 and air quality. 13,14 This consequently benefits air quality prediction, and pollution mitigation policy devising and aligns with one of the emphases in the theme of sustainable development. 46,47…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] These impacts depend on the aerosol physicochemical properties, which require detailed studies (i) to reduce the uncertainty in aerosol-cloud-climate interactions, one of the largest uncertainties in climate projection; 5,11 and (ii) to understand the various aerosol impacts on human health. [12][13][14] Numerous studies of laboratory experiments, field observations, and model simulations have examined aerosols to understand their fundamental properties, atmospheric transformation and impacts on climate and human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of fine PM from air to fetus is not fully understood. Although ultrafine particles contribute only to a small fraction of the total ambient PM mass, they are typically present in high concentrations in the urban atmosphere (3,(29)(30)(31) and have a high probability to deposit in the pulmonary system after inhalation than large particles (32,33). Through blood circulation and endocytosis, ultrafine particles likely enter organs beyond the lungs, such as the reproductive tract, heart, liver, spleen, kidneys, brain, and BAT (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Bondy et al (2018) performed a microscopy study on air samples collected from the south-eastern United States, and they found that most of the accumulation mode particles are internally mixed when the secondary organic aerosol concentration is high, and most of them are externally mixed during dust events. As one of the large mega-cities in China, Beijing has suffered from heavy air pollution (Yang et al, 2005) and is likely to have many factors affecting BC mixing state, which in turn has implications for both air quality and climate (Ching and Kajino, 2018). These aerosols can have a global reach (Liu et al, 2015) and as their effects may be influenced by dynamic effects near the point of emission where concentrations are highest, an polluted urban environment represents a good location to investigate these behaviours and properties.…”
Section: Introductionmentioning
confidence: 99%